Enforcement of Criminal Law against Land Grabbing Crimes in Indonesia - Ferdinan babo Pahana; Wahyu Prawesti; M. Yustino Aribawa (Civiliza Publishing, 2026)
Land is an important asset that has high economic, social, and cultural value for the people of Indonesia. The high value of land often triggers land conflicts, one of which is in the form of land grabbing. Land grabbing is an unlawful act carried out by controlling, occupying, or transferring rights to land belonging to others without the permission of the rightful party. This article aims to analyze law enforcement against the crime of land grabbing and examine the application of criminal sanctions based on Article 385 of the Criminal Code. The research method used is normative legal research with a legislative and conceptual approach. Legal materials are obtained through literature studies that include laws and regulations, legal literature, and relevant scientific journals. The results of the study show that although there are legal arrangements that regulate the crime of land grabbing, law enforcement still faces various obstacles, such as weak coordination between agencies, complexity of evidence, and the tendency to resolve land conflicts that overlap between criminal and civil channels. Therefore, it is necessary to strengthen more consistent criminal law enforcement, accompanied by preventive efforts through land registration and increasing public legal awareness to ensure certainty and legal protection of land rights.